Role of matrix metalloproteinases in the sequelae of dental caries- A review - Dr. RAMAPRABHA MDS,; Dr. SHALINI, (International Journal of Pharma and Bio Sciences, 2019)
Dental caries is an infectious microbial disease characterized by demineralization of inorganic component and destruction of the organic component. Demineralization is carried out by the microbial acids and destruction of the organic component was thought to be solely by the microbial proteolytic enzymes. But current evidence shows the decisive role played by the host derived matrix metalloproteinases (MMPs) in the progression of dental caries. Matrix metalloproteinases (MMPs) are a group of more than 25 secreted and membrane bound enzymes that represent class of enzymes responsible for degradation of all kinds of extracellular matrix proteins. This controlled degradation of the extracellular matrix is essential for normal embryological development of dental components, differentiation, modulation of the cell behavior and maintenance of homeostasis. They play an important role in dentine matrix formation, modulating caries progression and secondary dentine formation. They also have a destructive role in progression of dental caries, pulpal inflammation and periapical lesions. Their presence in root canal exudate, dentinal fluid, pulpal and periapical tissues can act as a biochemical indicator to assess the inflammatory status. Their levels also increase with inflammation and subsides on treatment.Thus, they have a potential role as a biomarker. This review summarizes the basics of MMPs its structure and classification, cysteine switch mechanism of activation, role of MMPs in the sequelae of dental caries, pulpal inflammation, periapical lesion progression their presence in dentinal fluid, saliva, root canal exudate and also a note on its role as a biomarker in the field of endodontics.